2019
DOI: 10.1016/j.scitotenv.2019.06.151
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of spray drift potential reduction for hollow-cone nozzles: Part 2. LiDAR technique

Abstract: Pesticide spray drift poses health hazards to humans and causes a significant impact on the environment. In this work the capacity of an ad hoc light detection and ranging (LiDAR) system to differentiate spray nozzles according to their potential drift risk is evaluated for the first time.A total of 23 drift potential tests using 10 hollow-cone nozzles were carried out with the sprayer kept in a static position. Drift potential reduction (DPR) values of between 88.6% and 93.6% were obtained when comparing stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
1
14
0
1
Order By: Relevance
“…The aim of the research conducted by Gregorio et al was to evaluate the drift reduction potential for hollow cone nozzles using light detection and ranging (LiDAR) technology. Based on the analysis of the results of this work, it was concluded that the LiDAR technique is an advantageous alternative in the evaluation of spray drift potential reduction [23,24].…”
Section: Introductionmentioning
confidence: 96%
“…The aim of the research conducted by Gregorio et al was to evaluate the drift reduction potential for hollow cone nozzles using light detection and ranging (LiDAR) technology. Based on the analysis of the results of this work, it was concluded that the LiDAR technique is an advantageous alternative in the evaluation of spray drift potential reduction [23,24].…”
Section: Introductionmentioning
confidence: 96%
“…On the contrary, the small droplets have excellent adhesion, coverage density and uniformity on the crop surface. However, they are prone to drift, which causes environmental pollution as well as damage to other crops nearby [10][11][12][13]. According to the theory of Biological Optimum Droplet Size (BODS), the range of droplet size captured by different biological targets is different.…”
Section: Introductionmentioning
confidence: 99%
“…During recent years several devices, such as air conveying devices and anti-drift nozzles were proposed and tested [9], [11], together with electronic sensors to adjust the spray to the crop [10], [14, [13]. In this view, recycling sprayers appear to be very promising [21], [17], because they can recover part of the active ingredient thus reducing the real applied dose.…”
Section: Introductionmentioning
confidence: 99%